2006
DOI: 10.1159/000093094
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Treatment for Laryngeal Carcinomas

Abstract: The objective of this study was to evaluate the impact of different surgical treatments as well as of radiotherapy for laryngeal carcinomas on health-related quality of life (QL). In a prospective, randomized multicenter study (five university hospitals in Germany), a total of 146 patients with laryngeal carcinomas (UICC stages: I–IV) underwent different surgical treatments (32 total laryngectomies, 81 CO2 laser microsurgical partial laryngectomies, 33 open partial laryngectomies). Postoperative rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
14
1
4
Order By: Relevance
“…The data suggest stronger limitations in functioning following radio(chemo‐)therapy compared with surgery alone. This has also been described by previous studies for radiation therapy,43 while surgery, even total laryngectomy, seems to have less impact on health‐related quality of life and functioning 44, 45. Still, a comparison of functional outcome after surgery alone versus radio‐chemotherapy alone would have added more information but was not possible with the given data.…”
Section: Discussionsupporting
confidence: 69%
“…The data suggest stronger limitations in functioning following radio(chemo‐)therapy compared with surgery alone. This has also been described by previous studies for radiation therapy,43 while surgery, even total laryngectomy, seems to have less impact on health‐related quality of life and functioning 44, 45. Still, a comparison of functional outcome after surgery alone versus radio‐chemotherapy alone would have added more information but was not possible with the given data.…”
Section: Discussionsupporting
confidence: 69%
“…This has also been described by previous studies for radiation therapy, 43 while surgery, even total laryngectomy, seems to have less impact on health-related quality of life and functioning. 44,45 Still, a comparison of functional outcome after surgery alone versus radio-chemotherapy alone would have added more information but was not possible with the given data. Surprisingly, functional impairment seems to be more disturbed in patients of 60 years and younger than in the comparably older age group.…”
Section: Discussionmentioning
confidence: 99%
“…6,14À16 The health-related QOL (HR-QOL) after treatment for cancer of the larynx was evaluated by several authors. 10,14,[17][18][19][20][21][22][23][24][25][26][27][28] At first, it was expected that the vocal impairments resulting from the different modalities of treatment would be reflected in the patients' HR-QOL. However, several studies have shown that this relationship is not direct.…”
Section: Introductionmentioning
confidence: 99%